Pengelolaan Sumber Daya Manusia di MTs Muhammadiyah Lima Kaum Tanah Datar - Saputra, Roni; Jamilus, Jamilus (Lembaga Yasin AlSys, 2023)
This study aims to describe the principal's leadership obligations in upholding justice in schools. This research was conducted at MTS Muhammadiyah, Tanah Datar. The approach used in this research is a case study. The results of the study of the principal's leadership obligations in improving justice in schools at MTS Muhammadiyahinclude a good personal approach with all school stakeholders; Planning the school as optimally as possible, analyzing challenges, obstacles and opportunities in the future; establish good cooperation with all educators, have educational efforts through collaboration, provide opportunities to improve educator practice, and encourage educator involvement in supporting school programs. These results have implications for teachers maximizing existing facilities and infrastructure to maximize the learning process, and schools already have a strong culture.